State Development Plan 1962-63 Part II Appendices Tripura Administration - Planning Commission (Planning Commission, 1962)
Rs.33.00 lakhs have not been included in Health programme, the provision is required for implementation of Water Supply & Sewerage Schemes by the Agartala Municipality. Thus the provision shown against Local Bodies.
Tripura Administration